Effect of electron beam irradiation on microbiological safety and quality of chilled poultry meat from Kazakhstan - Uazhanova, Raushangul; Tungyshbayeva, Ulbala; Nurdaulet, Sungkar; Zhanbolat, Almas; Yusof, Yus Aniza; Seksenbay, Shakhsanam; Danko, Igor; Moldakhmetova, Zamzagul (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Ensuring the safety and extending the shelf life of chilled poultry meat is vital in modern poultry meat production, particularly given the recent increase in demand in this area. Chilled meat has a short shelf life, so producers have limited time to sell their products and must rely on various methods of extending shelf life. Compared with other non-thermal methods, electron beam irradiation is a new non-thermal meat preservation technique with low cost, avoidance of contamination, and antibacterial effects. In this study, we investigate the effect of electron beam irradiation on the microbiological and physicochemical quality of chilled poultry meat produced in Kazakhstan to assess its suitability for use in local food processing systems. The samples were electron-beam-treated at doses of 2, 4, 6, and 8 kGy and stored in a refrigerator. Microbiological and physicochemical property evaluations were carried out for a period of 14 days. Our results demonstrated a significant decrease in total aerobic and facultative anaerobic microorganisms, and no detectable levels of Salmonella spp. and Listeria monocytogenes in the irradiated samples. The pH measurements remained stable at low doses; in comparison, higher doses resulted in a slight decrease. Moisture, protein, fat, and ash content were also evaluated and showed minimal changes as functions of irradiation dose. Our results indicate that electron beam irradiation, particularly at a dose of 2–4 kGy, effectively improves microbiological safety and extends the shelf life of chilled poultry meat up to 5–6 days, making it a promising solution for the modern poultry meat industry.